2018
DOI: 10.1007/s00586-018-5748-0
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of chronic low back pain and lumbar deformities in patients with Parkinson’s disease: implications on spinal surgery

Abstract: LBP and lumbar degeneration are common in PD. Both are related to movement disorder symptoms. The knowledge about musculoskeletal conditions in Parkinson's disease is important for an interdisciplinary conservative or operative treatment decision of LBP. These slides can be retrieved under Electronic Supplementary Material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…9 Galazky et al observed that low back pain and lumbar degeneration were more frequently seen in PD compared to healthy controls. 6 Pain intensity and disability scores were associated with advanced PD. The hypokinetic subtype was more associated with pain intensity; the prevelance of lumbar arthrosis was 79.6%, scoliosis 38.8% and spondylolisthesis 24.1% in their study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…9 Galazky et al observed that low back pain and lumbar degeneration were more frequently seen in PD compared to healthy controls. 6 Pain intensity and disability scores were associated with advanced PD. The hypokinetic subtype was more associated with pain intensity; the prevelance of lumbar arthrosis was 79.6%, scoliosis 38.8% and spondylolisthesis 24.1% in their study.…”
Section: Discussionmentioning
confidence: 98%
“…Spinal deformities and motor movement disorders are responsible for this situation. 5,6 In addition, the treatment of spinal pathologies in these patients requires a special approach due to the accompanying deformities and motor disorders. Spinal stenosis and PD share common clinical neuromotor symptoms.…”
Section: Lumbar Spinal Stenosis In Parkinson's Diseasementioning
confidence: 99%
“…The patients usually present pain symptoms in different segments of the body, like pain in the shoulder resul-ting from adhesive capsulitis and joint pain in lower extremities (LE) 5,6 . The lumbar region is one of the segments of the body that are more affected and individuals with PD present higher rates of constant low back pain (LBP) of musculoskeletal origin when compared to individuals of the control group [6][7][8] . Patients commonly report pain, muscular tension or stiffness located below the costal margin and above gluteal fold, associated or not with pain in the LE 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In PD, the progression of the disease results in axial skeletal abnormalities such as scoliosis 10 , excessive neck flexion (dropped head) 11 , trunk flexion (camptocormia) 12 and Pisa's syndrome 13 , which may increase the risk of LBP. The intensity of LBP is associated with the severity of the PD motor signs and the more advanced stage of the disease 8 . LBP presents multifactorial impact and, besides the pain itself, it has wider consequences, like limitations in activity, participation restrictions, overload of caregivers, use of medical assistance resources and financial charges 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation